Perception of Hospital Food Service Workers Regarding Patient Safety Culture and Patient Identification Practice - Ika Ratna Palupi; Yeni Prawiningdyah; Annisa Luthfia Setyawening; Lutfia Amalia (Universitas Muhammadiyah Yogyakarta, 2022)
Implementing the 'Patient Identification' procedure during food distribution will ensure the right diet is served to the right patient. This study explored the perception of patient safety culture and its association with patient identification practices among hospital food service workers. We conducted a mixed method research in a Joint Commission International (JCI)-accredited hospital in Yogyakarta. Food service workers who received patient safety training and were responsible for distributing food in adult inpatient wards (n=76) participated in this study. Perception of patient safety culture was measured using a validated questionnaire and in-depth interview, whereas patient identification practice was observed directly using a checklist. Descriptive statistics and chi-square tests were employed. More than half (55.3%) of the subjects perceived overall patient safety culture well. However, 34.2% of the subjects performed substandard practice verifying the patient's identity (name, address, or medical record number) when delivering food. There was an insignificant association between the perception of patient safety and patient identification practice by food service workers (p>0.05), as some considered that patient identification was more appropriate to be performed by other health professions instead of food service workers. Nevertheless, nearly all (98,68%) food service workers perceived their duty to match the patient's name with the label on the food tray as important.